Usury (riba) in the financial system in Malaysia / Mohammad Syirazi Abu Sin … [et al.] - Abu Sin, Mohammad Syirazi; Mohd Nor, Syed Aiman Firdaus Syed; Azahar, Muhamad Daniel Hakimi; Mat, Muhammad; Razali, Muhammad Hushairie Fiqri (2023)
This paper examines the concept of usury in Islamic finance and its ethical implications. The purpose of this study is to explore various interpretations of riba (usury). Using literature review and case studies, this study analyzes various types of riba (usury) and their historical and cultural context. The study also examines the debate on usury including whether it refers to all forms of usury or just the interest charged on loans. This study also discusses the hot issue regarding usury. This study concludes with a proposal to eliminate usury in Islam and prevent usury from happening in life.